Religious Values in The Funeral Procession on The Datuk Wisdom - Samiran, Fahmil; Helfi, Helfi; Hendri, Hendri; Noor, Ahmad Yunus Mohd (KARSA Journal of Social and Islamic Culture, 2023)
In Minangkabau may not be the only custom that occurs Salingka Nagari, but each country has its unique features. This article describes the religious value of the Datuk burial process in Minangkabau. This study investigates the religious values in the traditional ceremony of the death of a Datuk called Osong Kapali. This study uses qualitative research with data collection using interviews and documentation methods. The first ceremony of Osong Kapali begins with baretong, mangkaji adaik, mancabiakan shroud, Osong Kapali, installation of adaik cloth, maroncak, natural speech, Manigo Ari. In the procession of Adat Osong Kapali there are religious values such as the value of worship, generosity, the value of trust and the value of gratitude for abun and sustenance.